IMPLEMENTATION OF THE MONTREAL CONVENTION IN INDONESIA’S AND AUSTRALIA’S AIR TRANSPORT LAWS ON CARRIER’S LIABILITY - Sabrie, Hilda Yunita (Veritas et Justitia, 2024)
The Montreal Convention of 1999 establishes the legal responsibilities of carriers on international flights and has been ratified by numerous countries, including Indonesia and Australia. However, unlike Australia, Indonesia has yet to update its laws and regulations to align with the Convention’s provisions on carrier liability. This legislative gap may result in significant losses for air transportation service users who experience damages from aircraft accidents. This research examines the extent to which the liability provisions of the Montreal Convention have been incorporated into the national legal frameworks of Indonesia and Australia. The analysis employs three methodological approaches: statutory analysis, conceptual examination, and comparative study. The findings highlight the need for Indonesia to amend its regulations on carriers’ limited liability to comply with the standards set by the Montreal Convention, considering Australia’s best practices in its legal framework.